Out of the dust. - Hesse, Karen (New York : Scholastic Press, 1997)
In a series of poems, fifteen-year-old Billie Jo relates the hardships of living on her family's wheat farm in Oklahoma during the dust bowl years of the Depression. Exquisitely written, this Newbery Medal-winner is a poetic, compelling, and often melancholy novel of a young girl growing up in the Oklahoma Dust Bowl during the Depression.
NP
Accelerated Reader AR
Maine Student Book Award 3rd place, 1998-1999 ; Newbery Medal, 1998
Keywords: Dust storms -- Juvenile fiction; Farm life -- Oklahoma -- Juvenile fiction; Depressions -- 1929 -- Juvenile fiction; Poetry -- Juvenile fiction; Newbery Medal; Oklahoma -- History -- 20th century -- Juvenile fiction; Historical fiction